Polycarbonate resin composition and molded article composed of the same
The polycarbonate resin composition, featuring a vibration-damping elastomer and phosphate compounds, addresses the lack of long-term vibration-damping in automotive components, ensuring sustained quietness in vehicles.
Patent Information
- Application Number
- JP2023171053
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-02
- Publication Date
- 2025-04-14
AI Technical Summary
Existing polycarbonate resin compositions used in automotive components lack long-term vibration-damping properties, which is essential for maintaining quietness in vehicles over extended periods.
A polycarbonate resin composition is developed, containing 5 to 50 parts by weight of a vibration-damping elastomer with specific block structures and at least one phosphate compound, which imparts excellent thermal stability, moisture resistance, and long-term vibration-damping properties.
The composition achieves excellent thermal stability and moisture resistance, along with sustained vibration-damping properties over time, contributing to the long-term quietness of vehicles.
Smart Images

Figure 2025062168000001 
Figure 2025062168000002 
Figure 2025062168000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polycarbonate resin composition which is excellent in thermal stability and moist heat resistance, and a molded article made therefrom has vibration damping properties and further has excellent long-term vibration damping properties, and to a molded article made therefrom. [Background technology]
[0002] In recent years, with the shift to electric vehicles and autonomous driving, the need for quieter interiors has increased. To quieten interiors, vibration-damping materials such as vibration-damping rubber sheets and sound-absorbing materials such as sound-absorbing felt are used. However, the use of these materials has the disadvantage of increasing the weight of the vehicle, that is, reducing fuel efficiency, so it is difficult to increase their use any further. Therefore, it is thought that giving vibration-damping properties, that is, the ability to absorb sound waves, to the components themselves used in the interior and exterior of automobiles can contribute to further quieting automobiles. The same is thought to be true for polycarbonate resin compositions used in some automobile components.
[0003] Techniques for imparting vibration-damping properties to polycarbonate resin compositions have been investigated in the past. These techniques involve adding a block copolymer consisting of a block derived from a polymer of an aromatic vinyl compound and a block derived from a polymer of a conjugated diene compound as a vibration-damping elastomer to impart vibration-damping properties (see Patent Documents 1 to 5). However, it has not been investigated whether the vibration-damping properties can be maintained for a long period of time. Therefore, a polycarbonate resin composition with excellent long-term vibration-damping properties is needed so that the interior of a car can be kept quiet even when the car is used for a long period of time. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2000-178429 A [Patent Document 2] JP 2000-265075 A [Patent Document 3] JP 2002-37974 A [Patent Document 4] JP 2002-60634 A [Patent Document 5] JP 2011-105801 A Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a polycarbonate resin composition which is excellent in thermal stability and moist heat resistance, and which provides a molded article made therefrom with vibration damping properties and which further has excellent long-term vibration damping properties, and a molded article made therefrom. [Means for solving the problem]
[0006] As a result of extensive research, the present inventors have found that the above-mentioned objects can be achieved by the following polycarbonate resin composition and a molded article made from the same. 1. A resin composition comprising 100 parts by weight of (A) polycarbonate resin (component A), 5 to 50 parts by weight of (B) a vibration-damping elastomer (component B), and 0.001 to 1 part by weight of (C) at least one compound (component C) selected from the group consisting of phosphate compounds excluding trimethyl phosphate (component C-1) and phosphonic acid esters (component C-2), wherein component B is a block copolymer containing a block derived from a polymer of an aromatic vinyl compound and a block derived from a polymer having isoprene or isobutylene as part of the monomer, and having a glass transition temperature in the range of -30°C to 10°C. 2. The resin composition according to item 1 above, wherein component B is a compound which is partially or completely hydrogenated and has a glass transition temperature in the range of -25°C to 5°C. 3. The resin composition according to item 1 or 2 above, wherein component C-1 is a phosphate metal salt having an acid value of 10 to 55 mgKOH / g, and component C-2 is a phosphonate ester having an acid value of 0.01 to 0.30 mgKOH / g. 4. The resin composition according to item 3 above, wherein component C-1 is stearyl acid phosphate zinc salt, and component C-2 is ethyl diethyl phosphonoacetate. 5. The resin composition according to any one of the preceding paragraphs 1 to 4, characterized in that it contains, per 100 parts by weight of component A, 10 to 200 parts by weight of at least one thermoplastic resin selected from the group consisting of (D) a graft copolymer obtained by graft polymerizing an aromatic vinyl monomer and a vinyl cyanide monomer onto a diene rubber polymer or a mixture of said graft copolymer and a copolymer of an aromatic vinyl monomer and a vinyl cyanide monomer (D-1), a graft copolymer obtained by graft polymerizing an aromatic vinyl monomer and a vinyl cyanide monomer onto an acrylic rubber polymer or a mixture of said graft copolymer and a copolymer of an aromatic vinyl monomer and a vinyl cyanide monomer (D-2), a copolymer of an aromatic vinyl monomer and a vinyl cyanide monomer (D-3) and a polyester resin (D-4). 6. A molded article made of the thermoplastic resin composition according to any one of items 1 to 5 above. 7. An automobile component made of the molded product described in the preceding paragraph 6. Effect of the Invention
[0007] INDUSTRIAL APPLICABILITY The resin composition of the present invention has excellent thermal stability and moist heat resistance, and molded articles made therefrom have vibration damping properties and excellent long-term vibration damping properties, and therefore can contribute to making the interiors of future electric vehicles and electric automobiles quieter over long-term use. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] (Component A: polycarbonate resin) The polycarbonate resin used as component A in the present invention is obtained by reacting a dihydric phenol with a carbonate precursor. Examples of the reaction method include an interfacial polymerization method, a melt transesterification method, a solid-phase transesterification method of a carbonate prepolymer, and a ring-opening polymerization method of a cyclic carbonate compound.
[0009] Representative examples of the dihydric phenols used herein include hydroquinone, resorcinol, 4,4'-biphenol, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)propane (commonly known as bisphenol A), 2,2-bis(4-hydroxy-3-methylphenyl)propane, 2,2-bis(4-hydroxyphenyl)butane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 2,2-bis(4-hydroxyphenyl)pentane, 4,4'-(p-phenylene) Examples of the dihydric phenol include 4,4'-(m-phenylenediisopropylidene)diphenol, 1,1-bis(4-hydroxyphenyl)-4-isopropylcyclohexane, bis(4-hydroxyphenyl)oxide, bis(4-hydroxyphenyl)sulfide, bis(4-hydroxyphenyl)sulfoxide, bis(4-hydroxyphenyl)sulfone, bis(4-hydroxyphenyl)ketone, bis(4-hydroxyphenyl)ester, bis(4-hydroxy-3-methylphenyl)sulfide, 9,9-bis(4-hydroxyphenyl)fluorene, and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene. The preferred dihydric phenol is a bis(4-hydroxyphenyl)alkane, and among them, bisphenol A is particularly preferred from the viewpoint of impact resistance and is widely used.
[0010] In the present invention, in addition to bisphenol A type polycarbonate, which is a general-purpose polycarbonate, it is possible to use special polycarbonates produced using other dihydric phenols as the A component.
[0011] For example, polycarbonates (homopolymers or copolymers) using 4,4'-(m-phenylenediisopropylidene)diphenol (hereinafter sometimes abbreviated as "BPM"), 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane (hereinafter sometimes abbreviated as "Bis-TMC"), 9,9-bis(4-hydroxyphenyl)fluorene and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene (hereinafter sometimes abbreviated as "BCF") as part or all of the dihydric phenol components are suitable for applications where dimensional changes due to water absorption and dimensional stability are particularly demanding. These dihydric phenols other than BPA are preferably used in an amount of 5 mol% or more, particularly 10 mol% or more, of the total dihydric phenol components constituting the polycarbonate.
[0012] In particular, when high rigidity and better hydrolysis resistance are required, it is particularly suitable that the component A constituting the resin composition is a copolymer polycarbonate of the following (1) to (3). (1) A copolymer polycarbonate in which, relative to 100 mol % of the dihydric phenol component constituting the polycarbonate, BPM is 20 to 80 mol % (more preferably 40 to 75 mol %, and even more preferably 45 to 65 mol %) and BCF is 20 to 80 mol % (more preferably 25 to 60 mol %, and even more preferably 35 to 55 mol %). (2) A copolymer polycarbonate in which, relative to 100 mol % of the dihydric phenol component constituting the polycarbonate, BPA is 10 to 95 mol % (more preferably 50 to 90 mol %, and even more preferably 60 to 85 mol %) and BCF is 5 to 90 mol % (more preferably 10 to 50 mol %, and even more preferably 15 to 40 mol %). (3) A copolymer polycarbonate in which, relative to 100 mol % of the dihydric phenol component constituting the polycarbonate, BPM is 20 to 80 mol % (more preferably 40 to 75 mol %, and even more preferably 45 to 65 mol %) and Bis-TMC is 20 to 80 mol % (more preferably 25 to 60 mol %, and even more preferably 35 to 55 mol %).
[0013] These special polycarbonates may be used alone or in a suitable mixture of two or more kinds, or may be used in a mixture with the commonly used bisphenol A type polycarbonate.
[0014] The production methods and properties of these special polycarbonates are described in detail in, for example, JP-A-6-172508, JP-A-8-27370, JP-A-2001-55435 and JP-A-2002-117580.
[0015] Among the various polycarbonates mentioned above, those in which the copolymerization composition or the like is adjusted to bring the water absorption rate and Tg (glass transition temperature) into the ranges (i) or (ii) below have good hydrolysis resistance of the polymer itself and are also remarkably excellent in terms of low warpage after molding, and are therefore particularly suitable in fields where dimensional stability is required. (i) Polycarbonate having a water absorption rate of 0.05 to 0.15%, preferably 0.06 to 0.13%, and a Tg of 120 to 180°C. (ii) Polycarbonate having a Tg of 160 to 250° C., preferably 170 to 230° C., and a water absorption of 0.10 to 0.30%, preferably 0.13 to 0.30%, more preferably 0.14 to 0.27%.
[0016] The water absorption rate of polycarbonate is a value measured by using a disk-shaped test piece having a diameter of 45 mm and a thickness of 3.0 mm and measuring the moisture content after immersing it in water at 23°C for 24 hours in accordance with ISO62-1980. Also, Tg (glass transition temperature) is a value determined by differential scanning calorimetry (DSC) measurement in accordance with JIS K7121.
[0017] The carbonate precursor may be a carbonyl halide, a carbonic acid diester or a haloformate, and specific examples thereof include phosgene, diphenyl carbonate or a dihaloformate of a dihydric phenol.
[0018] When the dihydric phenol and carbonate precursor are used to produce a polycarbonate resin by interfacial polymerization, a catalyst, a terminal terminator, an antioxidant for preventing oxidation of the dihydric phenol, etc. may be used as necessary. The polycarbonate resin of the present invention includes a branched polycarbonate resin copolymerized with a trifunctional or higher polyfunctional aromatic compound, a polyester carbonate resin copolymerized with an aromatic or aliphatic (including alicyclic) bifunctional carboxylic acid, a copolymerized polycarbonate resin copolymerized with a bifunctional alcohol (including alicyclic), and a polyester carbonate resin copolymerized with such a bifunctional carboxylic acid and a bifunctional alcohol. The polycarbonate resin may also be a mixture of two or more of the obtained polycarbonate resins.
[0019] The branched polycarbonate resin can impart drip prevention properties to the resin composition of the present invention. Examples of trifunctional or higher polyfunctional aromatic compounds used in such branched polycarbonate resins include phloroglucin, phloroglucide, 4,6-dimethyl-2,4,6-tris(4-hydroxyphenyl)heptene-2,2,4,6-trimethyl-2,4,6-tris(4-hydroxyphenyl)heptane, 1,3,5-tris(4-hydroxyphenyl)benzene, 1,1,1-tris(4-hydroxyphenyl)ethane, 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane, 2,6-bis(2-hydroxy-5-methylbenzyl)-4-methylphenol, 4-{4-[1,1-bis(4- Examples of the trisphenols include trisphenols such as 1,4-dimethylbenzylphenol, tetra(4-hydroxyphenyl)methane, bis(2,4-dihydroxyphenyl)ketone, 1,4-bis(4,4-dihydroxytriphenylmethyl)benzene, trimellitic acid, pyromellitic acid, benzophenonetetracarboxylic acid, and acid chlorides thereof. Among these, 1,1,1-tris(4-hydroxyphenyl)ethane and 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane are preferred, and 1,1,1-tris(4-hydroxyphenyl)ethane is particularly preferred.
[0020] The constituent units derived from a polyfunctional aromatic compound in the branched polycarbonate preferably account for 0.01 to 1 mol %, more preferably 0.05 to 0.9 mol %, and even more preferably 0.05 to 0.8 mol %, based on a total of 100 mol % of the constituent units derived from a dihydric phenol and the constituent units derived from such a polyfunctional aromatic compound.
[0021] In particular, in the case of the melt transesterification method, branched structural units may be generated as a side reaction, and the amount of such branched structural units is preferably 0.001 to 1 mol %, more preferably 0.005 to 0.9 mol %, and even more preferably 0.01 to 0.8 mol %, based on the total of 100 mol % including the structural units derived from the dihydric phenol. 1 It can be calculated by H-NMR measurement.
[0022] The aliphatic difunctional carboxylic acid is preferably an α,ω-dicarboxylic acid. Examples of the aliphatic difunctional carboxylic acid include linear saturated aliphatic dicarboxylic acids such as sebacic acid (decanedioic acid), dodecanedioic acid, tetradecanedioic acid, octadecanedioic acid, and icosane diacid, and alicyclic dicarboxylic acids such as cyclohexane dicarboxylic acid. The bifunctional alcohol is more preferably an alicyclic diol, such as cyclohexane dimethanol, cyclohexane diol, and tricyclodecane dimethanol.
[0023] The reaction modes of the method for producing the polycarbonate resin of the present invention, such as the interfacial polymerization method, the melt transesterification method, the carbonate prepolymer solid-phase transesterification method, and the ring-opening polymerization method of a cyclic carbonate compound, are well known in various literatures and patent publications.
[0024] The melt volume rate (300° C., 1.2 kg load) of the polycarbonate resin in the present invention is not particularly limited, but is preferably 1 to 60 cm 3 / 10min, more preferably 3 to 30cm 3 / 10min, more preferably 5-20cm 3 / 10min. The melt volume rate is 1cm 3 Resin compositions obtained from polycarbonate resins having a melt volume rate of less than 60 cm / 10 min may be inferior in versatility due to poor fluidity during injection molding. 3 Polycarbonate resins with a melt volume rate of more than 100 / min may not have good mechanical properties. Melt volume rate is also called "MVR" and is measured in accordance with ISO1133.
[0025] The viscosity average molecular weight (M) of the polycarbonate resin in the present invention is preferably 24,000 or less, more preferably 22,500 or less, and even more preferably 20,000 or less. If the viscosity average molecular weight exceeds 24,000, the flowability is poor, so that in order to obtain a thin-walled molded product with a thickness of 1 to 3 mm, the molding conditions must be high temperature, and the resin or coloring agent may become prone to thermal decomposition. Furthermore, the lower limit of the viscosity average molecular weight is not particularly limited, but from the viewpoint of impact resistance, it is preferable that it is 14,000 or more. The viscosity average molecular weight (M) in the present invention is first calculated by the specific viscosity (η SP ) was measured at 20°C using an Ostwald viscometer from a solution of 0.7 g of polycarbonate resin in 100 ml of methylene chloride. Specific viscosity (η SP )=(t-t0) / t0 [t0 is the number of seconds that methylene chloride falls, and t is the number of seconds that the sample solution falls] The specific viscosity (η SP ) and calculate the viscosity average molecular weight M using the following formula. η SP / c=[η]+0.45×[η] 2 c (where [η] is the intrinsic viscosity) [η]=1.23×10 -4 M 0.83 c=0.7
[0026] The polycarbonate resin of the present invention may be a polycarbonate-polydiorganosiloxane copolymer resin. The polycarbonate-polydiorganosiloxane copolymer resin is preferably a copolymer resin prepared by copolymerizing a dihydric phenol represented by the following general formula (1) and a hydroxyaryl-terminated polydiorganosiloxane represented by the following general formula (3).
[0027] [ka]
[0028] [In the above general formula (1), R 1 and R 2 each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of each, they may be the same or different, e and f each represent an integer of 1 to 4, and W represents a single bond or at least one group selected from the group consisting of groups represented by the following general formula (2):
[0029] [ka]
[0030] [In the above general formula (2), R 11 ,R 12 ,R 13 ,R 14 ,R 15 ,R 16 ,R 17 and R 18each independently represents a group selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms; R 19 and R 20 each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 10 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of groups, they may be the same or different, g is an integer from 1 to 10, and h is an integer from 4 to 7.
[0031] [ka]
[0032] [In the above general formula (3), R 3 , R 4 , R 5 , R 6 , R 7 and R 8 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms; R 9 and R 10 are each independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, p is a natural number, q is 0 or a natural number, and p+q is a natural number of 10 to 300. X is a divalent aliphatic group having 2 to 8 carbon atoms.]
[0033] Examples of the dihydric phenol (I) represented by the general formula (1) include 4,4'-dihydroxybiphenyl, bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 2,2-bis(4-hydroxy-3,3'-biphenyl)propane, 2,2- Bis(4-hydroxy-3-isopropylphenyl)propane, 2,2-bis(3-t-butyl-4-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)octane, 2,2-bis(3-bromo-4-hydroxyphenyl)propane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, 2,2-bis(3-cyclohexyl-4-hydroxyphenyl)propane, 1,1-bis(3-cyclohexyl-4-hydroxyphenyl)cyclohexane, bis(4-hydroxyphenyl)propane, 4,4'-dihydroxydiphenylmethane, 9,9-bis(4-hydroxyphenyl)fluorene, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)cyclopentane, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxy-3,3'-dimethyldiphenyl ether, 4,4'-sulfonyldiphenol, 4,4'-dihydroxydiphenyl sulfoxide, 4,4'-dihydroxydiphenyl sulfide, 2,2'- Dimethyl-4,4'-sulfonyldiphenol, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfoxide, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfide, 2,2'-diphenyl-4,4'-sulfonyldiphenol, 4,4'-dihydroxy-3,3'-diphenyldiphenyl sulfoxide, 4,4'-dihydroxy-3,3'-diphenyldiphenyl sulfide, 1,3-bis{2-(4-hydroxyphenyl)propyl}benzene, 1,4-bis{2-(4-hydroxyphenyl)propyl}benzene, 1,Examples of the cyclohexane derivatives include 4-bis(4-hydroxyphenyl)cyclohexane, 1,3-bis(4-hydroxyphenyl)cyclohexane, 4,8-bis(4-hydroxyphenyl)tricyclo[5.2.1.02,6]decane, 4,4'-(1,3-adamantanediyl)diphenol, and 1,3-bis(4-hydroxyphenyl)-5,7-dimethyladamantane.
[0034] Among these, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 4,4'-sulfonyldiphenol, 2,2'-dimethyl-4,4'-sulfonyldiphenol, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,3-bis{2-(4-hydroxyphenyl)propyl}benzene, and 1,4-bis{2-(4-hydroxyphenyl)propyl}benzene are preferred, and 2,2-bis(4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane (BPZ), 4,4'-sulfonyldiphenol, and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene are particularly preferred. Among these, 2,2-bis(4-hydroxyphenyl)propane, which has excellent strength and good durability, is most suitable. These may be used alone or in combination of two or more kinds.
[0035] As the hydroxyaryl-terminated polydiorganosiloxane represented by the above general formula (3), for example, the compounds shown below are suitably used.
[0036] [ka]
[0037] Hydroxyaryl-terminated polydiorganosiloxane (II) is easily produced by hydrosilylation reaction of phenols having an olefinic unsaturated carbon-carbon bond, preferably vinylphenol, 2-allylphenol, isopropenylphenol, or 2-methoxy-4-allylphenol, with the end of a polysiloxane chain having a predetermined degree of polymerization. Among them, (2-allylphenol)-terminated polydiorganosiloxane and (2-methoxy-4-allylphenol)-terminated polydiorganosiloxane are preferred, and (2-allylphenol)-terminated polydimethylsiloxane and (2-methoxy-4-allylphenol)-terminated polydimethylsiloxane are particularly preferred. The molecular weight distribution (Mw / Mn) of the hydroxyaryl-terminated polydiorganosiloxane (II) is preferably 3 or less. In order to achieve even better low outgassing properties during high-temperature molding and low-temperature impact properties, the molecular weight distribution (Mw / Mn) is more preferably 2.5 or less, and even more preferably 2 or less. If the upper limit of this preferred range is exceeded, the amount of outgassing during high-temperature molding will be large, and low-temperature impact resistance may be poor.
[0038] Furthermore, in order to achieve a high level of impact resistance, the diorganosiloxane polymerization degree (p+q) of the hydroxyaryl-terminated polydiorganosiloxane (II) is suitably 10 to 300. The diorganosiloxane polymerization degree (p+q) is preferably 10 to 200, more preferably 12 to 150, and even more preferably 14 to 100. Below the lower limit of this preferred range, the impact resistance that is a characteristic of the polycarbonate-polydiorganosiloxane copolymer is not effectively exhibited, while above the upper limit of this preferred range, poor appearance appears.
[0039] The polydiorganosiloxane content in the total weight of the polycarbonate-polydiorganosiloxane copolymer resin is preferably 0.1 to 50% by weight. The polydiorganosiloxane content is more preferably 0.5 to 30% by weight, and even more preferably 1 to 20% by weight. At or above the lower limit of this preferred range, excellent impact resistance and flame retardancy are obtained, while at or below the upper limit of this preferred range, a stable appearance that is not easily affected by molding conditions is easily obtained. The polydiorganosiloxane polymerization degree and polydiorganosiloxane content are 1 It can be calculated by H-NMR measurement.
[0040] In the present invention, the hydroxyaryl-terminated polydiorganosiloxane (II) may be used alone or in combination of two or more kinds. In addition, comonomers other than the dihydric phenol (I) and hydroxyaryl-terminated polydiorganosiloxane (II) may be used in an amount of up to 10% by weight based on the total weight of the copolymer, provided that the use does not interfere with the present invention.
[0041] In the present invention, a mixed solution containing an oligomer having a terminal chloroformate group is prepared in advance by reacting a dihydric phenol (I) with a carbonate-forming compound in a mixed solution of a water-insoluble organic solvent and an aqueous alkaline solution.
[0042] In producing an oligomer of the dihydric phenol (I), the entire amount of the dihydric phenol (I) used in the method of the present invention may be converted into an oligomer at once, or a part of it may be added as a post-added monomer as a reaction raw material to the interfacial polycondensation reaction in the latter stage. The post-added monomer is added to quickly advance the polycondensation reaction in the latter stage, and there is no need to add it if it is not necessary.
[0043] The method of this oligomer formation reaction is not particularly limited, but it is usually preferable to carry out the reaction in a solvent in the presence of an acid binder.
[0044] The proportion of the carbonate ester-forming compound used may be appropriately adjusted in consideration of the stoichiometric ratio (equivalent) of the reaction. When a gaseous carbonate ester-forming compound such as phosgene is used, it is preferable to employ a method of blowing it into the reaction system.
[0045] As the acid binder, for example, an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide, an alkali metal carbonate such as sodium carbonate or potassium carbonate, an organic base such as pyridine, or a mixture thereof can be used. The proportion of the acid binder used can be appropriately determined in consideration of the stoichiometric ratio (equivalent) of the reaction, as described above. Specifically, it is preferable to use 2 equivalents or a slightly excess amount of the acid binder relative to the number of moles of the dihydric phenol (I) used to form the oligomer (usually 1 mole corresponds to 2 equivalents).
[0046] As the solvent, a solvent inert to various reactions, such as those used in the production of known polycarbonates, may be used alone or as a mixed solvent. Representative examples include hydrocarbon solvents such as xylene, and halogenated hydrocarbon solvents such as methylene chloride and chlorobenzene. In particular, halogenated hydrocarbon solvents such as methylene chloride are preferably used.
[0047] The reaction pressure for oligomer formation is not particularly limited, and may be normal pressure, elevated pressure, or reduced pressure, but it is usually advantageous to carry out the reaction under normal pressure. The reaction temperature is selected from the range of -20 to 50°C, and in many cases, since heat is generated during polymerization, it is desirable to cool the reaction with water or ice. The reaction time depends on other conditions and cannot be generally specified, but is usually carried out for 0.2 to 10 hours. The pH range for the oligomer formation reaction is the same as that of known interfacial reaction conditions, and the pH is always adjusted to 10 or more.
[0048] In the present invention, after obtaining a mixed solution containing an oligomer of dihydric phenol (I) having terminal chloroformate groups in this manner, the mixed solution is stirred while adding hydroxyaryl-terminated polydiorganosiloxane (II) represented by general formula (3) that has been highly refined to a molecular weight distribution (Mw / Mn) of 3 or less to the dihydric phenol (I), and the hydroxyaryl-terminated polydiorganosiloxane (II) and the oligomer are subjected to interfacial polycondensation to obtain a polycarbonate-polydiorganosiloxane copolymer.
[0049] In carrying out the interfacial polycondensation reaction, an acid binder may be appropriately added in consideration of the stoichiometric ratio (equivalent) of the reaction. For example, alkali metal hydroxides such as sodium hydroxide and potassium hydroxide, alkali metal carbonates such as sodium carbonate and potassium carbonate, organic bases such as pyridine, or mixtures thereof, are used as the acid binder. Specifically, when the hydroxyaryl-terminated polydiorganosiloxane (II) used or a part of the dihydric phenol (I) as described above is added to this reaction stage as a post-added monomer, it is preferable to use 2 equivalents or more of alkali relative to the total mole number of the post-added dihydric phenol (I) and the hydroxyaryl-terminated polydiorganosiloxane (II) (usually 1 mole corresponds to 2 equivalents).
[0050] The polycondensation by the interfacial polycondensation reaction between the oligomer of the dihydric phenol (I) and the hydroxyaryl-terminated polydiorganosiloxane (II) is carried out by vigorously stirring the above mixture.
[0051] In such a polymerization reaction, a terminal terminator or a molecular weight regulator is usually used. Examples of the terminal terminator include compounds having a monovalent phenolic hydroxyl group, such as ordinary phenol, p-tert-butylphenol, p-cumylphenol, tribromophenol, etc., as well as long-chain alkylphenols, aliphatic carboxylic acid chlorides, aliphatic carboxylic acids, hydroxybenzoic acid alkyl esters, hydroxyphenyl alkyl acid esters, and alkyl ether phenols. The amount of the terminal terminator is in the range of 100 to 0.5 mol, preferably 50 to 2 mol, relative to 100 mol of all dihydric phenol compounds used, and it is naturally possible to use two or more compounds in combination.
[0052] To accelerate the polycondensation reaction, a catalyst such as a tertiary amine, such as triethylamine, or a quaternary ammonium salt may be added. The reaction time of such a polymerization reaction is preferably 30 minutes or more, more preferably 50 minutes or more. If desired, a small amount of an antioxidant such as sodium sulfite or hydrosulfide may be added.
[0053] A branching agent can be used in combination with the above dihydric phenol compound to produce a branched polycarbonate-polydiorganosiloxane. Examples of polyfunctional aromatic compounds having three or more functional groups that can be used in such branched polycarbonate-polydiorganosiloxane copolymer resins include phloroglucin, phloroglucide, 4,6-dimethyl-2,4,6-tris(4-hydroxyphenyl)heptene-2,2,4,6-trimethyl-2,4,6-tris(4-hydroxyphenyl)heptane, 1,3,5-tris(4-hydroxyphenyl)benzene, 1,1,1-tris(4-hydroxyphenyl)ethane, 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane, 2,6-bis(2-hydroxy-5-methylbenzyl)-4-methylphenol, 4-{4-[1 Examples of the hydroxyphenyl ether include trisphenols such as {α,α-dimethylbenzylphenol}-α-dimethylbenzylphenol, tetra(4-hydroxyphenyl)methane, bis(2,4-dihydroxyphenyl)ketone, 1,4-bis(4,4-dihydroxytriphenylmethyl)benzene, trimellitic acid, pyromellitic acid, benzophenonetetracarboxylic acid, and acid chlorides thereof. Among these, 1,1,1-tris(4-hydroxyphenyl)ethane and 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane are preferred, and 1,1,1-tris(4-hydroxyphenyl)ethane is particularly preferred. The proportion of the polyfunctional compound in the branched polycarbonate-polydiorganosiloxane copolymer resin is preferably 0.001 to 1 mol %, more preferably 0.005 to 0.9 mol %, further preferably 0.01 to 0.8 mol %, and particularly preferably 0.05 to 0.4 mol %, based on the total amount of the polycarbonate-polydiorganosiloxane copolymer resin. 1 It can be calculated by H-NMR measurement.
[0054] The reaction pressure may be reduced, normal, or increased, but is usually preferably normal pressure or the reaction system's own pressure. The reaction temperature is selected from the range of -20 to 50°C, and in many cases, since heat is generated during polymerization, it is desirable to cool the reaction system with water or ice. The reaction time varies depending on other conditions such as the reaction temperature and cannot be generally specified, but is usually carried out for 0.5 to 10 hours.
[0055] In some cases, the obtained polycarbonate-polydiorganosiloxane copolymer resin is subjected to a suitable physical treatment (mixing, fractionation, etc.) and / or chemical treatment (polymer reaction, crosslinking treatment, partial decomposition treatment, etc.) to obtain a desired reduced viscosity [η SP It can also be obtained as a polycarbonate-polydiorganosiloxane copolymer resin of formula [1 / c].
[0056] The resulting reaction product (crude product) can be subjected to various post-treatments such as known separation and purification methods to recover a polycarbonate-polydiorganosiloxane copolymer resin of a desired purity (degree of purification).
[0057] The average size of the polydiorganosiloxane domains in the polycarbonate-polydiorganosiloxane copolymer resin molded article is preferably in the range of 1 to 40 nm. Such an average size is more preferably 1 to 30 nm, and even more preferably 5 to 25 nm. Below the lower limit of such a suitable range, impact resistance and flame retardancy may not be sufficiently exhibited, and above the upper limit of such a suitable range, impact resistance may not be stably exhibited. This provides a resin composition with excellent impact resistance and appearance.
[0058] The average domain size of the polydiorganosiloxane domains of the polycarbonate-polydiorganosiloxane copolymer resin molded product of the present invention was evaluated by small angle X-ray scattering (SAXS). Small angle X-ray scattering is a method for measuring diffuse scattering and diffraction occurring in a small angle region within a scattering angle (2θ) of <10°. In this small angle X-ray scattering method, if there are regions with different electron densities of about 1 to 100 nm in a substance, the diffuse scattering of X-rays is measured based on the electron density difference. The particle size of the measurement object is determined based on the scattering angle and scattering intensity. In the case of a polycarbonate-polydiorganosiloxane copolymer resin that has an aggregate structure in which polydiorganosiloxane domains are dispersed in a polycarbonate polymer matrix, the electron density difference between the polycarbonate matrix and the polydiorganosiloxane domains causes diffuse scattering of X-rays. The scattering intensity I at each scattering angle (2θ) in the range of scattering angles (2θ) less than 10° is measured to measure the small-angle X-ray scattering profile, and assuming that the polydiorganosiloxane domains are spherical domains and that there is variation in particle size distribution, a simulation is performed using commercially available analysis software from a tentative particle size and a tentative particle size distribution model to determine the average size of the polydiorganosiloxane domains. The small-angle X-ray scattering method allows the average size of the polydiorganosiloxane domains dispersed in the matrix of a polycarbonate polymer, which cannot be accurately measured by observation with a transmission electron microscope, to be measured accurately, simply, and with good reproducibility. The average domain size means the number average of the individual domain sizes. The term "average domain size" used in relation to the present invention refers to a measurement value obtained by measuring a 1.0 mm thick part of a three-stage plate prepared by the method described in the Examples using the small-angle X-ray scattering method. In addition, the analysis is performed using an isolated particle model that does not take into account interparticle interactions (interparticle interference).
[0059] (Component B: vibration-damping elastomer) Component B of the present invention is a block copolymer containing a block derived from a polymer of an aromatic vinyl compound and a block derived from a polymer having isoprene or isobutylene as part of the monomer, and is a component that imparts vibration-damping properties to the resin composition.
[0060] Examples of the aromatic vinyl compound include styrene, α-methylstyrene, p-methylstyrene, and tert-butylstyrene, and among these, styrene is preferred.
[0061] Examples of blocks derived from polymers having isoprene or isobutylene as a part of the monomer include isoprene homopolymers, isobutylene homopolymers, isoprene-isobutylene copolymers, random copolymers containing isoprene or isobutylene as one of the monomers, block copolymers containing isoprene or isobutylene as one of the blocks in the polymer molecule, and blocks derived from hydrogenated products obtained by hydrogenating them. Alternatively, blocks derived from other monomer components may be included, such as blocks derived from isoprene-butadiene copolymers and hydrogenated products thereof. Among these, blocks derived from hydrogenated products of polymers containing isoprene as a part of the monomer are preferred, and blocks derived from hydrogenated products of isoprene homopolymers are more preferred.
[0062] The molar ratio of the block derived from a polymer of an aromatic vinyl compound and the block derived from a polymer having isoprene or isobutylene as a part of the monomer is preferably 50 / 50 to 5 / 95, more preferably 40 / 60 to 10 / 90. If it is more than 50 / 50, the effect of improving vibration damping may be insufficient, and if it is less than 5 / 95, the compatibility with component A may be poor.
[0063] The glass transition temperature of component B, measured by the method described in the Examples, is in the range of -30°C to 10°C, preferably in the range of -25°C to 5°C, and more preferably in the range of -20°C to 0°C. When the glass transition temperature is in this range, the frequency range generated in automobiles, i.e., 10 1 ~10 5 It exhibits vibration-damping properties against vibrations and noise in the range of 100 Hz.
[0064] The content of component B is 5 to 50 parts by weight, preferably 7 to 40 parts by weight, and more preferably 10 to 30 parts by weight, relative to 100 parts by weight of component A. If the content of component B is less than 5 parts by weight, the vibration damping improving effect is insufficient, and if it exceeds 50 parts by weight, the rigidity required for an automotive resin member is not obtained.
[0065] (Component C: at least one compound selected from the group consisting of phosphate compounds excluding trimethyl phosphate and phosphonate ester compounds) The component C of the present invention is at least one compound selected from the group consisting of phosphate compounds (component C-1) excluding trimethyl phosphate and phosphonate compounds (component C-2).
[0066] (C-1 component) The C-1 component of the present invention is a phosphate compound other than trimethyl phosphate.Specific examples include tributyl phosphate, tricresyl phosphate, triphenyl phosphate, diphenyl cresyl phosphate, diphenyl mono orthoxenyl phosphate, tributoxyethyl phosphate, diisopropyl phosphate, stearyl acid phosphate, and their metal salts (phosphate metal salts).Among them, phosphate metal salts are preferred, stearyl stearyl acid phosphate metal salts are more preferred, and stearyl acid phosphate zinc salts are more preferred.
[0067] The acid value of the phosphate metal salt is preferably 10 to 55 mgKOH / g, more preferably 10 to 53 mgKOH / g, and even more preferably 30 to 53 mgKOH / g. If the acid value is less than 10 mgKOH / g, it is not practical to manufacture the phosphate metal salt, and if the acid value is more than 55 mgKOH / g, discoloration and strength reduction during molding may not be prevented. The acid value was measured using an indicator titration method, and a 2-ethylhexanol solution of the phosphate metal salt was titrated with a KOH alcohol solution at 60°C. The color was confirmed using phenolphthalein as an indicator.
[0068] (C-2 component) The C-2 component of the present invention is a phosphonate ester. Examples of phosphonate esters include phosphonate monoesters, phosphonate diesters, and phosphonate triesters, with phosphonate triesters being preferred. Various combinations of esters with carbon numbers ranging from 1 to 22 can be used, with ethyl diethyl phosphonoacetate being more preferred. The acid value of the phosphonate ester is preferably 0.01 to 0.30 mgKOH / g, more preferably 0.01 to 0.20 mgKOH / g, and even more preferably 0.05 to 0.15 mgKOH / g. An acid value of less than 0.01 mgKOH / g is not practical in terms of production, and an acid value of more than 0.30 mgKOH / g may not be able to prevent discoloration and strength loss during molding. The acid value was measured using a potentiometric titration device, and an alcohol solution of the phosphonate ester was titrated with an alcohol solution of KOH.
[0069] The content of component C is 0.001 to 1 part by weight, preferably 0.005 to 0.5 parts by weight, and more preferably 0.01 to 0.3 parts by weight, relative to 100 parts by weight of component A. When the content of component C is less than 0.001 part by weight or exceeds 1 part by weight, the effect of improving the damping properties and the moist heat resistance is insufficient.
[0070] (Component D: Thermoplastic resin) The resin composition of the present invention may contain, as component D, at least one thermoplastic resin selected from the group consisting of a graft copolymer obtained by graft polymerizing an aromatic vinyl monomer and a vinyl cyanide monomer onto a diene rubber polymer or a mixture of the graft copolymer and a copolymer of an aromatic vinyl monomer and a vinyl cyanide monomer (D-1), a graft copolymer obtained by graft polymerizing an aromatic vinyl monomer and a vinyl cyanide monomer onto an acrylic rubber polymer or a mixture of the graft copolymer and a copolymer of an aromatic vinyl monomer and a vinyl cyanide monomer (D-2), a copolymer of an aromatic vinyl monomer and a vinyl cyanide monomer (D-3), and a polyester resin (D-4).
[0071] (D-1 component) Component D-1 is a graft copolymer obtained by graft polymerizing an aromatic vinyl monomer and a vinyl cyanide monomer onto a diene rubber polymer, or a mixture of the graft copolymer and a copolymer of an aromatic vinyl monomer and a vinyl cyanide monomer.
[0072] As the diene rubber polymer, for example, rubber components such as polybutadiene, polyisoprene, and styrene-butadiene copolymer are used, and the proportion of the diene rubber polymer in component D-1, per 100 parts by weight of component D-1, is preferably 13 parts by weight at the lower limit, more preferably 14 parts by weight, and even more preferably 15 parts by weight at the upper limit, and is preferably 45 parts by weight at the upper limit.
[0073] Examples of aromatic vinyl monomers include styrene, α-methylstyrene, o-methylstyrene, p-methylstyrene, vinylxylene, ethylstyrene, dimethylstyrene, p-tert-butylstyrene, vinylnaphthalene, methoxystyrene, monobromostyrene, dibromostyrene, fluorostyrene, and tribromostyrene, with styrene being particularly preferred.
[0074] Examples of the vinyl cyanide monomer include acrylonitrile and methacrylonitrile, with acrylonitrile being particularly preferred.
[0075] The ratio of each component in the copolymer of aromatic vinyl monomer and vinyl cyanide monomer is preferably 95 to 50 parts by weight, more preferably 85 to 65 parts by weight, and preferably 5 to 50 parts by weight, more preferably 15 to 35 parts by weight, of the aromatic vinyl monomer, when the total is taken as 100 parts by weight. In addition, as the initiator, chain transfer agent, etc. used in the reaction, various conventionally known ones can be used as necessary, and they may be produced by any of the methods of bulk polymerization, suspension polymerization, and emulsion polymerization.
[0076] (D-2 component) Component D-2 is a graft copolymer obtained by graft polymerizing an aromatic vinyl monomer and a vinyl cyanide monomer onto an acrylic rubber polymer, or a mixture of said graft copolymer and a copolymer of an aromatic vinyl monomer and a vinyl cyanide monomer.
[0077] The acrylic rubber polymer is composed mainly of an acrylic acid alkyl ester, and may further contain other copolymerizable components such as styrene, methyl methacrylate, butadiene, and silicone, as necessary. Preferred examples of the acrylic acid alkyl ester include 2-ethylhexyl acrylate and n-butyl acrylate, and the content of such an acrylic acid alkyl ester in 100 parts by weight of the acrylic rubber polymer component is preferably 50 parts by weight or more.
[0078] Examples of aromatic vinyl monomers include styrene, α-methylstyrene, o-methylstyrene, p-methylstyrene, vinylxylene, ethylstyrene, dimethylstyrene, p-tert-butylstyrene, vinylnaphthalene, methoxystyrene, monobromostyrene, dibromostyrene, fluorostyrene, and tribromostyrene, with styrene being particularly preferred.
[0079] Examples of the vinyl cyanide monomer include acrylonitrile and methacrylonitrile, with acrylonitrile being particularly preferred.
[0080] The ratio of each component in the copolymer of aromatic vinyl monomer and vinyl cyanide monomer is preferably 95 to 50 parts by weight, more preferably 85 to 65 parts by weight, and preferably 5 to 50 parts by weight, more preferably 15 to 35 parts by weight, of the aromatic vinyl monomer, when the total is taken as 100 parts by weight. In addition, as the initiator, chain transfer agent, etc. used in the reaction, various conventionally known ones can be used as necessary, and they may be produced by any of the methods of bulk polymerization, suspension polymerization, and emulsion polymerization.
[0081] (D-3 component) The D-3 component is a copolymer of an aromatic vinyl monomer and a vinyl cyanide monomer. Examples of aromatic vinyl monomers include styrene, α-methylstyrene, o-methylstyrene, p-methylstyrene, vinylxylene, ethylstyrene, dimethylstyrene, p-tert-butylstyrene, vinylnaphthalene, methoxystyrene, monobromostyrene, dibromostyrene, fluorostyrene, and tribromostyrene, with styrene being particularly preferred. Examples of the vinyl cyanide monomer include acrylonitrile and methacrylonitrile, with acrylonitrile being particularly preferred.
[0082] (D-4 component) Component D-4 is a polyester resin, and among the dicarboxylic acid components and diol components that form the polyester, it is preferably a polyester resin in which 70 mol % or more of 100 mol % of the dicarboxylic acid components are aromatic dicarboxylic acids, more preferably 90 mol % or more, and most preferably 99 mol % or more.
[0083] Examples of the dicarboxylic acid include terephthalic acid, isophthalic acid, 2-chloroterephthalic acid, 2,5-dichloroterephthalic acid, 2-methylterephthalic acid, 4,4-stilbene dicarboxylic acid, 4,4-biphenyl dicarboxylic acid, orthophthalic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, bisbenzoic acid, bis(p-carboxyphenyl)methane, anthracene dicarboxylic acid, 4,4-diphenyl ether dicarboxylic acid, 4,4-diphenoxyethane dicarboxylic acid, 5-Na sulfoisophthalic acid, and ethylene-bis-p-benzoic acid. These dicarboxylic acids can be used alone or in combination of two or more. In addition to the aromatic dicarboxylic acids, the polyester resin of the present invention can be copolymerized with less than 30 mol% of an aliphatic dicarboxylic acid component. Specific examples thereof include adipic acid, sebacic acid, azelaic acid, dodecanedioic acid, 1,3-cyclohexane dicarboxylic acid, and 1,4-cyclohexane dicarboxylic acid.
[0084] Examples of the diol component of the present invention include ethylene glycol, diethylene glycol, 1,2-propylene glycol, 1,3-propanediol, 2,2-dimethyl-1,3-propanediol, trans- or cis-2,2,4,4-tetramethyl-1,3-cyclobutanediol, 1,4-butanediol, neopentyl glycol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, decamethylene glycol, cyclohexanediol, p-xylenediol, bisphenol A, tetrabromobisphenol A, and tetrabromobisphenol A-bis(2-hydroxyethyl ether). These can be used alone or in combination of two or more. The dihydric phenol in the diol component is preferably 30 mol% or less.
[0085] Specific examples of polyester resins include polyethylene terephthalate (PET), polypropylene terephthalate, polybutylene terephthalate (PBT), polyhexylene terephthalate, polyethylene naphthalate (PEN), polybutylene naphthalate (PBN), polyethylene-1,2-bis(phenoxy)ethane-4,4'-dicarboxylate, and the like, as well as copolymer polyester resins such as polyethylene isophthalate / terephthalate copolymers and polybutylene terephthalate / isophthalate copolymers.
[0086] The end group structure of the polyester resin used in the present invention is not particularly limited, and the ratio of hydroxyl groups and carboxyl groups in the end groups may be approximately equal, or one of them may be more than the other. Furthermore, the end groups may be blocked by reacting with a compound having reactivity with the end groups.
[0087] The method for producing the polyester resin used in the present invention is carried out by polymerizing the dicarboxylic acid component and the diol component while heating in the presence of a polycondensation catalyst containing titanium, germanium, antimony, etc., according to a conventional method, and discharging the by-product water or lower alcohol out of the system. For example, germanium-based polymerization catalysts include germanium oxides, hydroxides, halides, alcoholates, phenolates, etc., and more specifically, germanium oxide, germanium hydroxide, germanium tetrachloride, tetramethoxygermanium, etc. can be exemplified. In the present invention, compounds such as manganese, zinc, calcium, magnesium, etc., which are used in the transesterification reaction, which is a step before polycondensation, can be used in combination, and after the transesterification reaction, such catalysts can be deactivated by a phosphoric acid or phosphorous acid compound, etc., to perform polycondensation. Furthermore, the method for producing the polyester resin can be either a batch method or a continuous polymerization method.
[0088] Among the above polyester resins, polyethylene terephthalate is particularly suitable. Polyethylene terephthalate is a polymer obtained by polycondensation reaction of terephthalic acid or a derivative thereof with 1,4-ethanediol or a derivative thereof, and also includes copolymers of other dicarboxylic acid components and other alkylene glycol components as described above.
[0089] The end group structure of the polyethylene terephthalate is not particularly limited as described above, but more preferably, the number of terminal carboxyl groups is less than the number of terminal hydroxyl groups. The above-mentioned various methods can be used for the production method, but continuous polymerization is preferable. This is because the quality stability is high and it is also advantageous in terms of cost. Furthermore, it is preferable to use an organic titanium compound as the polymerization catalyst. This is because it tends to have less effect on transesterification reactions. As preferable examples of such organic titanium compounds, titanium tetrabutoxide, titanium isopropoxide, titanium oxalate, titanium acetate, titanium benzoate, titanium trimellitate, and the reaction product of tetrabutyl titanate and trimellitic anhydride can be mentioned. The amount of the organic titanium compound used is preferably such that the titanium atom is 3 to 12 mg atomic % relative to the acid component constituting the polyethylene terephthalate.
[0090] The molecular weight of the polyester resin of the present invention is not particularly limited, but the intrinsic viscosity measured at 35° C. using o-chlorophenol as a solvent is preferably 0.5 to 1.5, and particularly preferably 0.6 to 1.2.
[0091] The content of component D is preferably 10 to 200 parts by weight, more preferably 15 to 150 parts by weight, and further preferably 20 to 100 parts by weight, relative to 100 parts by weight of component A. If the content of component D is less than 10 parts by weight, sufficient fluidity and chemical resistance may not be obtained, whereas if it exceeds 200 parts by weight, heat resistance and impact resistance may decrease.
[0092] <Other ingredients> The polycarbonate resin composition of the present invention may also contain a release agent, an ultraviolet absorber, a core-shell type graft polymer, a flame retardant, a filler, and the like.
[0093] (i) Release agent In order to further improve releasability from a mold during melt molding, the polycarbonate resin composition of the present invention may contain a mold release agent within a range that does not impair the object of the present invention. Examples of such release agents include higher fatty acid esters of monohydric or polyhydric alcohols, higher fatty acids, paraffin wax, beeswax, olefin waxes, olefin waxes containing a carboxy group and / or a carboxylic anhydride group, silicone oils, organopolysiloxanes, etc. As the higher fatty acid esters, partial or complete esters of monohydric or polyhydric alcohols having 1 to 20 carbon atoms and saturated fatty acids having 10 to 30 carbon atoms are preferred. Examples of the partial or complete ester of such monohydric or polyhydric alcohol and saturated fatty acid include monoglyceride stearic acid, diglyceride stearic acid, triglyceride stearic acid, monosorbitate stearic acid, stearyl stearate, monoglyceride behenic acid, behenyl behenate, pentaerythritol monostearate, pentaerythritol tetrastearate, pentaerythritol tetrapelargonate, propylene glycol monostearate, stearyl stearate, palmityl palmitate, butyl stearate, methyl laurate, isopropyl palmitate, biphenyl biphenate, sorbitan monostearate, and 2-ethylhexyl stearate. Among them, monoglyceride stearic acid, triglyceride stearic acid, pentaerythritol tetrastearate, and behenyl behenate are preferably used. As the higher fatty acid, saturated fatty acid having 10 to 30 carbon atoms is preferable. Such fatty acids include myristic acid, lauric acid, palmitic acid, stearic acid, behenic acid, and the like. These releasing agents may be used alone or in combination of two or more. The content of such releasing agents is preferably 0.01 to 5 parts by weight based on 100 parts by weight of component A.
[0094] (ii) Ultraviolet absorber The polycarbonate resin composition of the present invention can contain an ultraviolet absorber. Benzophenone-based examples include 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octoxybenzophenone, 2-hydroxy-4-benzyloxybenzophenone, 2-hydroxy-4-methoxy-5-sulfoxybenzophenone, 2-hydroxy-4-methoxy-5-sulfoxytrihydridyl benzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxy-5-sodium sulfoxybenzophenone, bis(5-benzoyl-4-hydroxy-2-methoxyphenyl)methane, 2-hydroxy-4-n-dodecyloxybenzophenone, and 2-hydroxy-4-methoxy-2'-carboxybenzophenone.Benzotriazoles include, for example, 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 2-(2-hydroxy-3,5-dicumylphenyl)phenylbenzotriazole, 2-(2-hydroxy-3-tert-butyl-5-methylphenyl)-5-chlorobenzotriazole, 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], 2-(2-hydroxy-3,5-di-tert-butylphenyl)benzotriazole, 2-(2-hydroxy-3,5-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2-hydroxy-3,5-di-tert-amylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, Examples of the copolymer include azole, 2-(2-hydroxy-5-tert-butylphenyl)benzotriazole, 2-(2-hydroxy-4-octoxyphenyl)benzotriazole, 2,2'-methylenebis(4-cumyl-6-benzotriazolephenyl), 2,2'-p-phenylenebis(1,3-benzoxazin-4-one), and 2-[2-hydroxy-3-(3,4,5,6-tetrahydrophthalimidomethyl)-5-methylphenyl]benzotriazole, as well as polymers having a 2-hydroxyphenyl-2H-benzotriazole skeleton, such as copolymers of 2-(2'-hydroxy-5-methacryloxyethylphenyl)-2H-benzotriazole and vinyl monomers copolymerizable with the monomer, and copolymers of 2-(2'-hydroxy-5-acryloxyethylphenyl)-2H-benzotriazole and vinyl monomers copolymerizable with the monomer.Examples of hydroxyphenyl triazines include 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-hexyloxyphenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-methyloxyphenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-ethyloxyphenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-propyloxyphenol, and 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-butyloxyphenol.Further examples include compounds in which the phenyl group of the above-mentioned compounds is replaced with a 2,4-dimethylphenyl group, such as 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl)-5-hexyloxyphenol. Examples of cyclic imino esters include 2,2'-p-phenylenebis(3,1-benzoxazin-4-one), 2,2'-(4,4'-diphenylene)bis(3,1-benzoxazin-4-one), and 2,2'-(2,6-naphthalene)bis(3,1-benzoxazin-4-one).
[0095] Examples of cyanoacrylates include 1,3-bis-[(2'-cyano-3',3'-diphenylacryloyl)oxy]-2,2-bis[(2-cyano-3,3-diphenylacryloyl)oxy]methyl)propane and 1,3-bis-[(2-cyano-3,3-diphenylacryloyl)oxy]benzene.
[0096] Furthermore, the ultraviolet absorber may be a polymer type ultraviolet absorber obtained by copolymerizing such an ultraviolet absorbing monomer and / or a light stable monomer having a hindered amine structure with a monomer such as an alkyl (meth)acrylate by adopting a structure of a radically polymerizable monomer compound. Suitable examples of the ultraviolet absorbing monomer include compounds containing a benzotriazole skeleton, a benzophenone skeleton, a triazine skeleton, a cyclic imino ester skeleton, and a cyanoacrylate skeleton in the ester substituent of a (meth)acrylic acid ester. The content of the ultraviolet absorber is preferably 0.01 to 2 parts by weight, more preferably 0.02 to 1.5 parts by weight, and even more preferably 0.03 to 1 part by weight, relative to 100 parts by weight of the A component.
[0097] (iii) Core-shell type graft polymer The polycarbonate resin composition of the present invention may contain a core-shell type graft polymer excluding component D. The core-shell type graft polymer is a graft copolymer in which a rubber component having a glass transition temperature of 10° C. or less is used as a core, and one or more monomers selected from aromatic vinyl, acrylic acid ester, methacrylic acid ester, and vinyl compounds copolymerizable therewith are copolymerized as a shell.
[0098] Examples of the rubber component of the core-shell type graft polymer include butadiene rubber, butadiene-acrylic composite rubber, acrylic rubber, acrylic-silicone composite rubber, isobutylene-silicone composite rubber, isoprene rubber, styrene-butadiene rubber, chloroprene rubber, ethylene-propylene rubber, nitrile rubber, ethylene-acrylic rubber, silicone rubber, epichlorohydrin rubber, fluororubber, and those with hydrogen added to the unsaturated bond portion thereof. However, from the viewpoint of the concern of the generation of harmful substances during combustion, rubber components that do not contain halogen atoms are preferable in terms of environmental load. The glass transition temperature of the rubber component is preferably -10°C or lower, more preferably -30°C or lower, and the rubber component is particularly preferably butadiene rubber, butadiene-acrylic composite rubber, acrylic rubber, or acrylic-silicone composite rubber. The composite rubber refers to a rubber obtained by copolymerizing two kinds of rubber components, or a rubber polymerized to have an IPN structure in which the components are intertwined with each other so that they cannot be separated. In the core-shell type graft polymer, the particle diameter of the core is preferably 0.05 to 0.8 μm, more preferably 0.1 to 0.6 μm, and even more preferably 0.15 to 0.5 μm, in terms of weight average particle diameter. If it is in the range of 0.05 to 0.8 μm, better impact resistance is achieved.
[0099] Examples of aromatic vinyls in the vinyl compounds copolymerized as the shell of the core-shell graft polymer with the rubber component include styrene, α-methylstyrene, p-methylstyrene, alkoxystyrene, and halogenated styrene. Examples of acrylic acid esters include methyl acrylate, ethyl acrylate, butyl acrylate, cyclohexyl acrylate, and octyl acrylate. Examples of methacrylic acid esters include methyl methacrylate, ethyl methacrylate, butyl methacrylate, cyclohexyl methacrylate, and octyl methacrylate, with methyl methacrylate being particularly preferred. Among these, it is particularly preferred to contain methacrylic acid esters such as methyl methacrylate as an essential component. This is because the core-shell graft polymer has excellent affinity with the polycarbonate resin, so that more rubber components are present in the resin, and the good impact resistance of the polycarbonate resin is more effectively exerted, resulting in good impact resistance of the resin composition. More specifically, the methacrylic acid ester is preferably contained in an amount of 10 parts by weight or more, more preferably 15 parts by weight or more, per 100 parts by weight of the graft component (per 100 parts by weight of the shell in the case of a core-shell type polymer). The elastic polymer containing a rubber component having a glass transition temperature of 10° C. or less may be produced by any of the polymerization methods of bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization, and the copolymerization method may be either one-stage grafting or multi-stage grafting. The polymer may also be a mixture with a copolymer of only the graft component that is a by-product during production. In addition to the general emulsion polymerization method, examples of the polymerization method include a soap-free polymerization method using an initiator such as potassium persulfate, a seed polymerization method, and a two-stage swelling polymerization method. In addition, in the suspension polymerization method, a method in which the aqueous phase and the monomer phase are held separately and both are accurately supplied to a continuous disperser, and the particle size is controlled by the rotation speed of the disperser, and a method in which the monomer phase is supplied to an aqueous liquid having dispersibility by passing it through a fine orifice or a porous filter having a diameter of several to several tens of μm to control the particle size in a continuous production method may be performed. In the case of a core-shell type graft polymer, the reaction may be one-stage or multi-stage for both the core and the shell.
[0100] Such polymers are commercially available and can be easily obtained. For example, those mainly made of butadiene rubber as a rubber component include Kane Ace M series manufactured by Kaneka Corporation (e.g., M-711 whose shell component is mainly made of methyl methacrylate, M-701 whose shell component is mainly made of methyl methacrylate and styrene), Metablen C series manufactured by Mitsubishi Rayon Co., Ltd. (e.g., C-223A whose shell component is mainly made of methyl methacrylate and styrene), E series (e.g., E-870A whose shell component is mainly made of methyl methacrylate and styrene), and Paraloid EXL series manufactured by Dow Chemical Co., Ltd. (e.g., EXL-2620 whose shell component is mainly made of methyl methacrylate). Examples of materials that have acrylic rubber or butadiene-acrylic composite rubber as the main component include the W series (for example, W-600A, whose shell component is mainly methyl methacrylate) and Dow Chemical's Paraloid EXL series (for example, EXL-2390, whose shell component is mainly methyl methacrylate), and materials that have acrylic-silicone composite rubber as the main component include Mitsubishi Rayon's Metablen S-2501, whose shell component is mainly methyl methacrylate, and SRK200A, whose shell component is mainly acrylonitrile-styrene.
[0101] (iv) Flame retardants The polycarbonate resin composition of the present invention may contain various compounds conventionally known as flame retardants for thermoplastic resins, particularly polycarbonate resins, but more preferably, (i) halogen-based flame retardants (e.g., brominated polycarbonate compounds, etc.), (ii) phosphorus-based flame retardants (e.g., monophosphate compounds, phosphate oligomer compounds, phosphonate oligomer compounds, phosphonitrile oligomer compounds, phosphonic acid amide compounds, and phosphazene compounds, etc.), (iii) metal salt-based flame retardants (e.g., organic sulfonic acid alkali (earth) metal salts, boric acid metal salt-based flame retardants, and stannic acid metal salt-based flame retardants, etc.), and (iv) silicone-based flame retardants consisting of silicone compounds. The incorporation of compounds used as flame retardants not only improves flame retardancy, but also improves, for example, antistatic properties, fluidity, rigidity, and thermal stability based on the properties of each compound.
[0102] The content of the flame retardant is preferably 0.01 to 30 parts by weight, more preferably 0.05 to 28 parts by weight, and further preferably 0.08 to 25 parts by weight, relative to 100 parts by weight of component A. If the content of the flame retardant is less than 0.01 part by weight, sufficient flame retardancy may not be obtained, whereas if it exceeds 30 parts by weight, mechanical properties may be significantly reduced.
[0103] (v) Filling material In the polycarbonate resin composition of the present invention, a conventionally known inorganic filler can be used, but the filler to be preferably used is at least one filler selected from the group consisting of needle-shaped inorganic fillers, fibrous inorganic fillers, and plate-shaped inorganic fillers. The needle-shaped inorganic fillers are inorganic fillers having a whisker-like or columnar shape, and are selected from wollastonite, boehmite, and the like. The fibrous inorganic fillers refer to inorganic fillers having a thin and long fibrous shape, and are selected from glass fibers, metal fibers, ceramic fibers, and the like. The plate-shaped inorganic fillers are inorganic fillers having a flake-like or scaly shape, and are selected from talc, mica, glass flakes, and the like. Among the above inorganic fillers, glass fibers, talc, mica, and wollastonite are particularly preferred.
[0104] (Glass fiber) The glass fiber is not particularly limited to a glass composition such as A glass, C glass, or E glass, and may contain TiO2, SO3, P2O5, or other components. However, E glass (alkali-free glass) is more preferable. The glass fiber is formed by quenching molten glass while stretching it using various methods to form a specific fiber shape. The quenching and stretching conditions in such cases are not particularly limited. In addition, the cross-sectional shape may be a perfect circle, or may be an ellipse, cocoon, or three-lobe shape other than a perfect circle. Furthermore, a mixture of a perfect circle glass fiber and a shape other than a perfect circle glass fiber may be used.
[0105] The fiber diameter of the glass fiber is preferably 1 to 25 μm, and more preferably 3 to 17 μm. If the fiber diameter is too small, the fiber is easily broken and the rigidity is easily reduced. In addition, the surface area is large, so a relatively large amount of coating agent is required, which is likely to have an adverse effect when flame retardancy is required. If the fiber diameter is too large, the appearance of the molded product is likely to be deteriorated.
[0106] The fiber length of the glass fiber is preferably 50 to 500 μm, more preferably 100 to 400 μm, and even more preferably 120 to 300 μm as the number average fiber length in the pellet or molded product made of the resin composition of the present invention. The number average fiber length is a value calculated by an image analyzer from an optical microscope observation of the glass fiber residue collected after dissolving the molded product in a solvent or decomposing the resin with a basic compound. In addition, when calculating this value, the value is based on a method in which fibers with a length of 10 μm or less are not counted.
[0107] Examples of the plate-like glass filler include glass flakes including metal-coated glass flakes and metal oxide-coated glass flakes. The glass flakes that serve as the substrate of the plate-like glass filler are plate-like glass fillers manufactured by a cylinder blowing method, a sol-gel method, or the like. The size of the raw material of such glass flakes can be selected from a variety of sizes depending on the degree of crushing and classification. The average particle size of the glass flakes used as the raw material is preferably 10 to 1000 μm, more preferably 20 to 500 μm, and even more preferably 30 to 300 μm. This is because those in the above range are excellent in both handleability and moldability. Usually, plate-like glass fillers are cracked by melt-kneading with resin, and the average particle size becomes smaller. The number average particle size of the plate-like glass filler in the resin composition is preferably 10 to 200 μm, more preferably 15 to 100 μm, and even more preferably 20 to 80 μm. The number-average particle size is a value calculated by an image analyzer from an image of the residue of the plate-shaped glass filler collected by high-temperature incineration of the molded product, dissolution with a solvent, decomposition with a chemical, etc., observed under an optical microscope. The value is calculated by a method in which flake thickness is used as a guide and flakes with a length less than the flake thickness are not counted. The thickness is preferably 0.5 to 10 μm, more preferably 1 to 8 μm, and even more preferably 1.5 to 6 μm. The plate-shaped glass filler having the above number-average particle size and thickness achieves good mechanical strength, appearance, and moldability.
[0108] The glass filler is preferably surface-treated with a known surface treatment agent, such as a silane coupling agent, a titanate coupling agent, or an aluminate coupling agent, from the viewpoint of improving mechanical strength. Glass fibers (including those coated with metal or metal oxide) and glass flakes (including those coated with metal or metal oxide) are preferably bundled with olefin resins, styrene resins, acrylic resins, polyester resins, epoxy resins, urethane resins, or the like. The amount of the bundled filler is preferably 0.5 to 8 parts by weight, more preferably 1 to 4 parts by weight, per 100 parts by weight of the filler.
[0109] Furthermore, the fibrous glass filler and plate-like glass filler of the present invention include those surface-coated with different materials. Suitable examples of such different materials include metals and metal oxides. Examples of metals include silver, copper, nickel, and aluminum. Examples of metal oxides include cerium oxide, zirconium oxide, iron oxide, aluminum oxide, and silicon oxide. The method of surface-coating such different materials is not particularly limited, and examples thereof include various known plating methods (e.g., electrolytic plating, electroless plating, hot-dip plating, etc.), vacuum deposition, ion plating, CVD (e.g., thermal CVD, MOCVD, plasma CVD, etc.), PVD, and sputtering.
[0110] (talc) The talc in the present invention is a hydrous magnesium silicate in terms of chemical composition, generally represented by the chemical formula 4SiO2·3MgO·2H2O, and is usually a scaly particle with a layered structure, and is composed of 56 to 65 parts by weight of SiO2, 28 to 35 parts by weight of MgO, and about 5 parts by weight of H2O. Other minor components include 0.03 to 1.2 parts by weight of Fe2O3, 0.05 to 1.5 parts by weight of Al2O3, 0.05 to 1.2 parts by weight of CaO, 0.2 parts by weight or less of K2O, and 0.2 parts by weight or less of Na2O. The particle size of the talc is preferably in the range of 0.1 to 15 μm (more preferably 0.2 to 12 μm, even more preferably 0.3 to 10 μm, and particularly preferably 0.5 to 5 μm) in terms of average particle size measured by a sedimentation method. Furthermore, it is particularly preferable to use talc with a bulk density of 0.5 (g / cm3) or more as the raw material. The average particle size of talc refers to D50 (median diameter of particle size distribution) measured by X-ray transmission method, which is one of the liquid phase precipitation methods. A specific example of an apparatus for performing such measurements is Sedigraph 5100 manufactured by Micromeritics.
[0111] There is no particular limitation on the manufacturing method when talc is pulverized from raw stones, and axial flow mill method, annular mill method, roll mill method, ball mill method, jet mill method, and container rotation type compression shear mill method can be used. Furthermore, the talc after pulverization is preferably classified by various classifiers, and the distribution of particle diameter is uniform. There is no particular limitation on the classifier, and examples thereof include impactor type inertial force classifiers (variable impactor, etc.), Coanda effect type inertial force classifiers (elbow jet, etc.), centrifugal field classifiers (multi-stage cyclone, microplex, dispersion separator, Accucut, turbo classifier, turboplex, micron separator, and super separator, etc.).
[0112] Furthermore, the talc is preferably in an aggregated state from the viewpoint of ease of handling, etc., and methods for producing the talc include a method using degassing compression, a method using a sizing agent for compression, etc. In particular, the method using degassing compression is preferred from the viewpoints of simplicity and of not mixing unnecessary sizing agent resin components into the resin composition of the present invention.
[0113] (Mica) The mica preferably has an average particle size of 10 to 100 μm as measured by a microtrack laser diffraction method. More preferably, the average particle size is 20 to 50 μm. If the average particle size of the mica is less than 10 μm, the effect of improving the rigidity is insufficient, and if it exceeds 100 μm, the improvement in rigidity is insufficient and the mechanical strength such as impact properties may be significantly reduced, which is not preferable. The mica preferably has a thickness of 0.01 to 1 μm as measured by observation with an electron microscope. More preferably, the thickness is 0.03 to 0.3 μm. The aspect ratio is preferably 5 to 200, more preferably 10 to 100. The mica used is preferably muscovite mica, and its Mohs hardness is about 3. Muscovite mica can achieve higher rigidity and higher strength than other micas such as phlogovite, and solves the problem of the present invention at a better level. The mica may be produced by either a dry grinding method or a wet grinding method. The dry grinding method is more common and has a lower cost, whereas the wet grinding method is effective for grinding the mica more thinly and finely, which results in a greater effect in improving the rigidity of the resin composition.
[0114] (Wollastonite) The fiber diameter of wollastonite is preferably 0.1 to 10 μm, more preferably 0.1 to 5 μm, and even more preferably 0.1 to 3 μm. The aspect ratio (average fiber length / average fiber diameter) is preferably 3 or more. The upper limit of the aspect ratio is 30 or less. Here, the fiber diameter is measured by observing the reinforcing filler with an electron microscope, determining the individual fiber diameters, and calculating the number average fiber diameter from the measured values. The electron microscope is used because it is difficult to accurately measure the size of the target level with an optical microscope. The fiber diameter is measured by randomly extracting the filler to be measured for the image obtained by observation with the electron microscope, measuring the fiber diameter near the center, and calculating the number average fiber diameter from the measured values. The magnification of the observation is about 1000 times, and the number of measured fibers is 500 or more (600 or less is suitable for work). On the other hand, the average fiber length is measured by observing the filler with an optical microscope, determining the individual lengths, and calculating the number average fiber length from the measured values. Observation with an optical microscope begins with preparing a sample in which the fillers are dispersed so that they do not overlap too much. Observation is performed with a 20x objective lens, and the observed image is captured as image data by a CCD camera with approximately 250,000 pixels. An image analyzer is used on the obtained image data, and the fiber length is calculated using a program that determines the maximum distance between two points on the image data. Under these conditions, the size per pixel corresponds to a length of 1.25 μm, and the number of fibers measured is 500 or more (600 or less is optimal for practical purposes).
[0115] In order to fully reflect the inherent whiteness of the wollastonite of the present invention in the resin composition, it is preferable to remove as much iron as possible from the raw ore and from the equipment wear during the crushing of the raw ore using a magnetic separator. The iron content in the wollastonite after the magnetic separator treatment is preferably 0.5 parts by weight or less, calculated as Fe2O3.
[0116] The content of the filler is preferably 1 to 100 parts by weight, more preferably 5 to 90 parts by weight, and further preferably 10 to 80 parts by weight, relative to 100 parts by weight of component A. If the content is less than 1 part by weight, the flexural modulus is poor and sufficient sustained antistatic properties may not be obtained, whereas if the content exceeds 100 parts by weight, the thermal stability may deteriorate and the molecular weight may decrease significantly during extrusion or molding.
[0117] (vi) Other additives In addition, the polycarbonate resin composition of the present invention may contain small amounts of additives known per se to impart various functions to the molded product or improve its properties. These additives may be added in normal amounts as long as they do not impair the object of the present invention. Examples of such additives include sliding agents (e.g., PTFE particles), antistatic agents, crystal nucleating agents, inorganic and organic antibacterial agents, photocatalytic antifouling agents (e.g., fine titanium oxide particles, fine zinc oxide particles), radical generators, infrared absorbing agents (heat ray absorbing agents), and photochromic agents.
[0118] <Method of producing resin composition> Any method can be used to produce the polycarbonate resin composition of the present invention. For example, each component and optionally other components are premixed, then melt-kneaded, and pelletized. Premixing means include a Nauta mixer, a V-type blender, a Henschel mixer, a mechanochemical device, and an extrusion mixer. In premixing, granulation can be performed using an extrusion granulator or a briquetting machine. After premixing, the mixture is melt-kneaded using a melt kneader such as a vented twin-screw extruder, and pelletized using a pelletizer or other device. Other examples of melt kneaders include a Banbury mixer, a kneading roll, and a thermostatic stirring vessel, but a vented twin-screw extruder is preferred. Alternatively, each component and optionally other components can be independently supplied to a melt kneader such as a twin-screw extruder without premixing.
[0119] <About molded products> The polycarbonate resin composition of the present invention obtained as described above can be used to produce various products by injection molding the pellets produced as described above. Furthermore, it is also possible to directly produce sheets, films, irregular extrusion molded products, and injection molded products from the resin melt-kneaded in an extruder without passing through pellets. In such injection molding, molded products can be obtained using injection molding methods such as injection compression molding, injection press molding, gas-assisted injection molding, foam molding (including injection of supercritical fluid), insert molding, in-mold coating molding, heat-insulating mold molding, rapid heating and cooling mold molding, two-color molding, sandwich molding, and ultra-high speed injection molding, in addition to ordinary molding methods, depending on the purpose. The advantages of these various molding methods are already widely known. In addition, molding can be performed using either the cold runner method or the hot runner method. In addition, the resin composition of the present invention can be used to mold various irregular extrusion molded products and sheets by extrusion molding.
[0120] For the molded article made of the resin composition of the present invention, the value of tan δ at -10°C to 10°C (10Hz) is important. Tan δ represents the ratio of storage shear modulus (G') to loss shear modulus (G''). The larger the value, the greater the energy absorption when the material is vibrated by sound waves, and the higher the vibration damping property. While a general resin to which no B component is added exhibits a tan δ of about 0.015, the tan δ of the resin composition of the present invention is preferably 0.02 or more, more preferably 0.03 or more, and even more preferably 0.035 or more. The reason for the temperature range of -10°C to 10°C (10Hz) is that the main noises of automobiles (motor noise, wind noise, road noise) are in the range of about 100 to 10,000Hz, and when converted into a temperature frequency (WLF conversion), it corresponds to a range of -10°C to 10°C at 10Hz.
[0121] In order to use the molded article as a resin member in an automobile, the rigidity of the molded article is preferably more than 1000 MPa, more preferably 1400 MPa or more, and even more preferably 1600 MPa or more. If the rigidity is less than 1000 MPa, problems such as deformation due to various mechanical inputs applied to the automobile may occur. EXAMPLES
[0122] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In addition, "parts" are parts by weight unless otherwise specified. In addition, evaluations were performed by the following methods.
[0123] <Evaluation of Resin Composition> 1. Glass transition temperature of vibration-damping elastomer (component B) Using a DSC device (Netzsch DSC214Polyma), the temperature was increased and decreased under the following processes and conditions a to c. From the plot of DSC (mW / mg) and temperature (°C) in process c, the temperature at which the slope changed, that is, Tg, was read. Note that the lower limit of effective measurement under these conditions was -40°C, and when Tg was lower than -40°C and undetectable, it was recorded as Tg<-40°C. a: 25℃→250℃ … 20℃ / min temperature increase and 5min hold b: 250℃→-60℃ … 100℃ / min temperature drop and hold for 7min c: -60℃→40℃ … 20℃ / min temperature increase
[0124] 2. Vibration damping properties of resin compositions (molded products) (1) Tan δ of untreated item For the ISO test dumbbell test pieces prepared by the method described below, tan δ was measured using a DMA device (Netzsch DMA242E_Artemis) at a frequency of 10 Hz and a temperature rise of 2°C / min. The tan δ values at -10°C, 0°C, and 10°C were read from the obtained graph, and their average values were calculated. Average tan δ values of 0.035 or more were marked with ◎, those between 0.02 and less than 0.035 were marked with ○, and those less than 0.02 were marked with ×. (2) Tan δ of heat-moisture treated product The average tan δ of the moist heat treated products was calculated by the same method as in "(1) Tan δ of unmoisture-heat treated products" below. The retention rate of tan δ after moist heat treatment relative to the tan δ of the unmoisture-heat treated products obtained in (1) was evaluated as ◎, 80% or more but less than 85% as ○, and less than 80% as ×.
[0125] 3. Rigidity of resin composition (molded product) The flexural modulus of the ISO dumbbell test specimens prepared by the method described below was measured at 2 mm / min in accordance with ISO178.
[0126] <Examples 1 to 28 and Comparative Examples 1 to 10> [Preparation of resin pellets] Based on the components and amounts shown in Tables 1 and 2, various compounding components were mixed using a tumbler and melt-kneaded at a cylinder temperature of 270°C using a twin-screw extruder (TEX30α, Japan Steel Works, Ltd.) to obtain various pellets.
[0127] [Production of dumbbell specimens for ISO testing by injection molding] The pellets obtained by the above method were dried in a hot air circulation dryer at 110°C for 5 hours, and then an injection molding machine (ROBOSHOT α-S100iA manufactured by FANUC Corporation) was used to mold ISO test dumbbell test pieces having a thickness of 4 mm, a width of 10 mm, and a length of 170 mm under the following conditions: cylinder temperature of 280°C and mold temperature of 80°C for Example 1, and cylinder temperature of 260°C and mold temperature of 60°C for all other examples.
[0128] [Heat and moisture treatment of dumbbell specimens for ISO testing] The ISO test dumbbell test pieces obtained by the above method were subjected to accelerated moist heat treatment for 96 hours under conditions of a temperature of 100°C and full humidity using a highly accelerated life tester (EHS-412MD, manufactured by Espec Corp.).
[0129] [raw materials] (Component A) A-1: Polycarbonate resin (Teijin Ltd. Panlite L-1225WP, viscosity average molecular weight: 22,400)
[0130] (B component) B-1: Vinyl-SEPS (HYBRAR7125F, manufactured by Kuraray Co., Ltd., Tg=-9°C) B-2: Vinyl-SEEPS (HYBRAR7311F, manufactured by Kuraray Co., Ltd., Tg=-19°C) B-3: Vinyl-SIS (HYBRAR5127 manufactured by Kuraray Co., Ltd., Tg=9°C) B-4: SIBS (SIBSTAR102T, manufactured by Kaneka Corporation, Tg=-25℃) B-5 (Comparative Example): SEBS (SEPTON 8006 manufactured by Kuraray Co., Ltd., Tg<-40°C) B-6 (Comparative Example): SEPS (SEPTON 2104 manufactured by Kuraray Co., Ltd., Tg < -40°C) B-7 (Comparative Example): SEEPS (SEPTON 4033 manufactured by Kuraray Co., Ltd., Tg < -40°C)
[0131] (C component) C-1: Stearyl acid phosphate zinc salt (purified with LBP-1830 from Sakai Chemical Industry Co., Ltd., acid value 49.9 mg KOH / g) C-2: Stearyl acid phosphate zinc salt (JP-518Zn, manufactured by Johoku Chemical Industry Co., Ltd., acid value 54.5 mg KOH / g) C-3: Stearyl acid phosphate zinc salt (Sakai Chemical Industry Co., Ltd. LBP-1830, acid value 56.6 mg KOH / g) C-4: Triethyl phosphonoacetate (JC-224, manufactured by Johoku Chemical Industry Co., Ltd., acid value 0.08 mg KOH / g) C-5: Triethyl phosphonoacetate (Solvay, acid value 0.39 mg KOH / g) C-6 (Comparative Example): Trimethyl phosphate (manufactured by Daihachi Chemical Co., Ltd.) C-7 (Comparative Example): Tris(2,4-di-tert-butylphenyl)phosphite (ADEKA STAB 2112 manufactured by ADEKA Corporation) C-8 (Comparative Example): n-Octadecyl-3-(4'-hydroxy-3',5'-di-t-butylphenyl)propionate (phenolic heat stabilizer AO-50 manufactured by ADEKA Corporation)
[0132] (D component) D-1: ABS resin (Magnum A371 manufactured by Trinseo) D-2: ASA resin (777K manufactured by INEOS Styrolution) D-3: AS resin (LiTac A BS-207, manufactured by Nippon A&L Co., Ltd.) D-4-1: PET resin (Teijin Ltd. TRN-8550FF) D-4-2: PBT resin (1100-211MD manufactured by Changchun Kako Co., Ltd.)
[0133] (Other ingredients) E-1: Acrylic-silicone composite rubber core-shell type graft polymer (Metablen S-2030 manufactured by Mitsubishi Chemical Corporation) E-2: Butadiene rubber core-shell type graft polymer (Kane Ace M711, manufactured by Kaneka Corporation) E-3: Pentaerythritol tetra fatty acid ester (NOF Corporation, Unistar H476S)
[0134] [Table 1]
[0135] [Table 2]
[0136] All of the examples shown in Tables 1 and 2 have good vibration damping properties before and after moist heat treatment, and the vibration damping properties do not decrease much even after moist heat treatment. Furthermore, they have the rigidity required for a resin, and can be used as resin materials that can contribute to quieter automobile interiors.
Claims
1. A resin composition comprising 100 parts by weight of (A) polycarbonate resin (component A), 5 to 50 parts by weight of (B) a vibration-damping elastomer (component B), and 0.001 to 1 part by weight of (C) at least one compound (component C) selected from the group consisting of phosphate compounds excluding trimethyl phosphate (component C-1) and phosphonic acid esters (component C-2), wherein component B is a block copolymer containing a block derived from a polymer of an aromatic vinyl compound and a block derived from a polymer having isoprene or isobutylene as a part of the monomer, and having a glass transition temperature in the range of -30°C to 10°C.
2. 2. The resin composition according to claim 1, wherein component B is a compound which is partially or completely hydrogenated and has a glass transition temperature in the range of -25°C to 5°C.
3. 3. The resin composition according to claim 1, wherein the C-1 component is a phosphate metal salt having an acid value of 10 to 55 mgKOH / g, and the C-2 component is a phosphonate ester having an acid value of 0.01 to 0.30 mgKOH / g.
4. 4. The resin composition according to claim 3, wherein the component C-1 is stearyl acid phosphate zinc salt, and the component C-2 is ethyl diethyl phosphonoacetate.
5. The resin composition according to claim 1 or 2, characterized in that it contains 10 to 200 parts by weight of at least one thermoplastic resin selected from the group consisting of (D) a graft copolymer obtained by graft polymerizing an aromatic vinyl monomer and a vinyl cyanide monomer onto a diene rubber polymer or a mixture of the graft copolymer and a copolymer of an aromatic vinyl monomer and a vinyl cyanide monomer (D-1), a graft copolymer obtained by graft polymerizing an aromatic vinyl monomer and a vinyl cyanide monomer onto an acrylic rubber polymer or a mixture of the graft copolymer and a copolymer of an aromatic vinyl monomer and a vinyl cyanide monomer (D-2), a copolymer of an aromatic vinyl monomer and a vinyl cyanide monomer (D-3) and a polyester resin (D-4) relative to 100 parts by weight of component A.
6. A molded article made of the thermoplastic resin composition according to claim 1 or 2.
7. An automobile component formed from the molded product according to claim 6.
Citation Information
Patent Citations
Damping thermoplastic resin composition
JP2000178429A
Vibration-damping thermoplastic resin composition
JP2000265075A
Vehicle exterior material highly resistant to chipping and impact
JP2002037974A
Vibration-damping thermoplastic resin composition
JP2002060634A
Thermoplastic resin composition and molded product
JP2011105801A